Male description and generic review of Agyrtolasia Szymczakowski, with key to genera of Agyrtodini (Coleoptera: Leiodidae: Camiarinae: Agyrtodini) - Seago, Ainsley E. (Zootaxa, 2005)
The male of Agyrtolasia calliptera Szymczakowski is described and new collecting records are provided. The range and habitat of Agyrtolasia resemble those of Australian Agyrtodes Portevin, with A. calliptera found in fungus and forest leaf litter from New South Wales to Southeast Queensland. Pertinent diagnostic and systematic characters are discussed for adult Agyrtodini. The probable phylogenetic placement of Agyrtolasia is very close to Agyrtodes; adult morphology suggests the former is either within or sister to the latter. An illustrated key to world agyrtodine genera is provided.